Profile [videorecording (DVD)] - Bekmambetov, Timur, 1961-; Kane, Valene, 1987-; Latif, Shazad, 1988-; Adams, Christine (Actress); Rahimzadeh, Amir, 1974-; Erelle, Anna (Focus Features, 2021)
An undercover British journalist risks her life by infiltrating militant extremist groups online.